MODEL PENILAIAN SIKAP SOSIAL SISWA SEKOLAH DASAR/MADRASAH IBTIDAIYAH MELALUI PENDEKATAN SURVEY KARAKTER DAN MEDIA DIGITAL - Amaliyah Amaliyah; Ahmad Hakam; Suci Nurpratiwi (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
The research aims to develop an attitude assesment model using online media. According to primary reseach by several Madrasah Ibtidaiyah YURJA teachers, conclude that they had difficult to assesment at social attitude because used online learning methods. Based on the research bakcground, needs to the develop a social attitude assesment model using online aplication, as an alternative assesment during the covid 19 pandemic. The research methode is literature review and development research, data collection techniques are questionnaries and documentation studies. The result is research is to describe the difficulties of Madrasah Ibtidaiyah teachers in assessing social attitudes, describe the types of social attitudes relevant to 21st century skills, and describe the steps to implement a social attitude assesment instrument trough online aplicaton, such as slido and video.